The association of serum vitamin D level and neonatal respiratory distress syndrome - Weili Liu; Pingping Xu (BMC, 2023)
Abstract Background Neonatal respiratory distress syndrome (NRDS) is a critical disease in premature infants. Vitamin D plays an important role in promoting the development of fetal lung structure and the formation of pulmonary surfactants. This study aimed to investigate the correlation between the serum 25(OH)D3 level in the cord blood of premature infants and the prognosis of NRDS. Methods This retrospective study recruited 82 preterm infants (gestational age 28-36 weeks) diagnosed with NRDS as the NRDS group, and 82 non-NRDS preterm infants as the control group, respectively. The diagnostic efficiency of 25(OH)D3 on NRDS was revealed by receiver operating characteristics curve (ROC) analysis. Enzyme linked immunosorbent assay (ELISA) was performed to evaluate the 25(OH)D3 level in the serum of the cord blood in preterm neonates. The NRDS risk indicators were identified by the multivariate logistic regression analysis. Results Cord blood 25(OH)D3 levels were significantly lower in NRDS preterm infants than control group infants. 25(OH)D3 levels in cord blood can be used to predict NRDS in preterm infants. In addition, 25(OH)D3 levels in cord blood were positively correlated with Apgar score (1 min/5 min) and negatively correlated with oxygen support/CPAP duration in preterm infants with NRDS. 25(OH)D3 in cord blood <57.69 nmol/L (24 ng/ml), gestational age <31 weeks, birth weight <1.86 kg, Apgar score (1 min) <7 and Apgar score (5 min) < 8 were independent risk factors for NRDS. Conclusion 25(OH)D3 level is an independent risk factor for NRDS in preterm infants.